The Influence of Packaging Design Elements of Cosmetic and Brand Ambassadors on Purchasing Decisions - Suharto, Imam; Verawaty, Verawaty; Irawan, Haris (Jurnal Mirai Management, 2023)
The research was used to determine The influence of Package Design Elements of Cosmetic Brand Ambassadors on Purchases Decision. This study uses a quantitative method descriptive approach, data obtained using a questionnaire via google form. The research population is cosmetic consumers including brand warda, mustika ratu, Ms Glow, Skintific, Hanasui, Azzura, Implora, Hanasui, Maybelline, in several major cities, the islands of Sulawesi, Kalimantan and Jabodetabek, to examine the influence of package design on consumer purchase decisions and the sample search was carried out by purposive sampling, which was successfully answered and could be used as many as 100 sempel. Research measurement with a 5-point Likert scale Total respondents who participated in answering the questionnaire consisting of housewives, workers, and students were 100 usable questionnaires. Data analysis using Smart PLS 4.0 (Hair et al., 2019) for hypothesis testing. using research instruments X1: Package design elements (CP), X2: Brand Ambassadors (SP) and Y: Purchase decision (PD). Result Element Package design has a positive effect on purchase decision and Brand Ambassador has a positive effect on purchase decision.